EXTRACTION AND ISOLATION OF COLLAGEN FROM THE SKINS OF BASA FISH (PANGASIUS HYPOPHTHALMUS) - Tuan, Phan Dinh; Thu Huong, Le Thi; Dzung, Nguyen Hoang (Vietnam Journal of Science and Technology, 2014)
Acid-solubilized collagen (ASC) was extracted from basa fish skin (Pangasius hypophthalmus) by acetic acid and purified by dialysis, lyophilization and super-critical (SC) CO2 extraction techniques. Dialysis yield for salt removal reached 93.3% in stirring condition at 24h, while the efficiency of lipid extraction process could reach 91.6% at conditions: Pressure- 200 bar, CO2 flow rate of 10g/min, temperature of 38oC, concentration of ethanol as co-solvent of 10% (v/v) and the retention time of 60 minutes. The obtained collagen has low impurities of lipid (0.33%), ashes (0.29%) and apprears to be of no smell, no color, high molecular weight, which is appropriate for cosmetic, pharmaceutical and food application. Keywords: basa fish, super critical CO2, Pangasius hypophthalmus